The sculpture of Ruth Asawa contours in the air - Burgard, Timothy Anglin; Cornell, Daniell; Jennings, Emily K. Doman; Ehrens, Susan; Harris, Mary Emma 1943-; Higa, Karin; Hoefer, Jacqueline; Karlstrom, Paul J. 1941-; Kreidler, John; Stauter, Susan; Terry, Colleen; Woodbridge, Sally Byrne 1930- (Fine Arts Museums of San Francisco, 2020)
The work of American artist Ruth Asawa (1926-2013) is brought into brilliant focus in this definitive book, originally published to accompany the first complete retrospective of Asawa's career, organized by the Fine Arts Museums of San Francisco in 2006. This new edition features an expanded collection of essays and a detailed illustrated chronology that explore Asawa's fascinating life and her lasting contributions to American art. Beginning with her earliest works-drawings and paintings created in the 1940s while studying at Black Mountain College-this volume traces Asawa's flourishing career in San Francisco and her trajectory as a pioneering modernist sculptor who is recognized internationally for her innovative wire sculptures, public commissions, and activism on behalf of public arts education. 0Through her lifelong experimentations with wire, especially its capacity to balance open and closed forms, Asawa invented a powerful new vocabulary that contributed a unique perspective to the field of twentieth-century abstract sculpture. Working in a variety of nontraditional media, Asawa performed a series of remarkable metamorphoses, leading viewers into a deeper awareness of natural forms by revealing their structural properties. Through her art, Asawa transfigured the commonplace into metaphors for life processes themselves. The Sculpture of Ruth Asawa establishes the importance of Asawa's work within a larger cultural context of artists who redefined art as a way of thinking and acting in the world, rather than as merely a stylistic practice
Impressum: This book was originally published by The Fine Arts Museums of San Francisco in association with the University of California Press on the occasion of the exhibition "The Sculpture of Ruth Asawa: Contours in the Air" at the de Young from 18 November 2006 to 28 January 2007, and at the Japanese American National Museum, Los Angeles, from 10 March to 27 May 2007
Keywords: Asawa, Ruth -- 1926-2013; Asawa, Ruth / Exhibitions; Asawa, Ruth / Criticism and interpretation; Asawa, Ruth; Criticism, interpretation, etc; Exhibition catalogs; Ausstellungskatalog -- De Young Museum -- 18.12.2006-28.06.2007 -- San Francisco, Calif.; Ausstellungskatalog -- Japanese American National Museum -- 10.03.2007-27.05.2007 -- Los Angeles, Calif.